Anaemia during pregnancy: a cross-sectional study of antenatal attendants at the Madina Pentecost Hospital, La Nkwantanang Municipality, Ghana - Richard Vikpebah Duneeh; Wina Ivy Ofori Boadu; Lois Tekutey Narh; Joseph Frimpong; Abdul-Wahab Mawuko; John Gameli Deku; Kofi Mensah; Charles Nkansah; Samuel Kwasi Appiah; Felix Osei Boakye; Enoch Odame Anto; Lilian Antwi Boateng; et al. (Cogent Public Health, 2024)
Although anaemia is a common life-threatening condition among pregnant women, particularly those in low-income countries, literature remains very limited in Ghana in general and particularly in the Madina La-Nkwantanang Municipality of the Greater Accra Region, where no studies have been done. This study, therefore, assessed anaemia in pregnant women attending the Pentecost Hospital in the La-Nkwantanang Municipality, Ghana. This cross-sectional study conveniently recruited 300 Ghanaian pregnant women attending the Madina Pentecost Hospital for antenatal care. A structured questionnaire was administered to obtain data on sociodemographics (age, marital status, level of education, occupation and religion) and knowledge level of anaemia. Blood samples were taken for an automated complete blood count (CBC). SPSS software version 26 and GraphPad Prism were used for the statistical analysis. The prevalence rate of anaemia was 211/300 (70.3%). 159 (75.4%) of the anaemic subjects presented with a mild anaemia form, 51(24.2%) presented with a moderate form, and 1(0.47%) presented with severe form. Normocytic normochromic anaemia was the dominant anaemia type (33.6%), followed by microcytic normochromic anaemia (27.0%), and then normocytic hypochromic (24.64%). Pregnant women within their third trimester recorded the highest incidence rates of both normocytic normochromic 34 (47.89%) and mild types 71 (44.65%) of anaemia. The prevalence of anaemia among pregnant women is overwhelmingly high with a preponderance towards those in their third trimester. As such, high-risk pregnant women should be well-monitored to prevent exacerbating the condition.